The role of the money market in financing commercial banks in Algeria during the period 2016-2019 - aid, lamine; zitouni, kamal (Journal of Research in Finance and Accounting, 2021)
This study is aiming to know the role of Monetary Market for financing monetary institutions and public treasury, and the input of this Market to support the economic growth by providing the necessary short-term cash flows between surplus owners and cash deficit owners. We achieved this study following a descriptive method for the theoretical side, and using the analytical approach for the practical side, which is about the Algerian Monetary Market, in the period 2016 and March 2019.